What is important to the decision to disclose nonsuicidal self-injury in formal and social contexts? - Mirichlis, Sylvanna; Boyes, Mark; Hasking, Penelope; Lewis, S.P. (2023)
Objective: Disclosure of nonsuicidal self-injury (NSSI) is associated with a range of both positive (e.g., help-seeking) and negative (e.g., discrimination) outcomes. The aim of this study was to assess the importance of a range of factors concerned with: NSSI experiences, self-efficacy to disclose self-injury, interpersonal factors, and reasons for or expectations of disclosure, to the decision to disclose self-injury to friends, family members, significant others, and health professionals. Methods: Three hundred seventy-one participants with lived experience of NSSI completed a survey in which they rated the importance of the aforementioned factors to the decision of whether to disclose NSSI to different people. A mixed-model analysis of variance was conducted to investigate whether the factors differed in importance and if this importance differed across relationship types. Results: All factors held importance, though to differing degrees, with those related to relationship quality being most important overall. Generally, factors relating to tangible aid were considered more important when considering disclosure to health professionals than to other people. Conversely, interpersonal factors, particularly trust, were more important when disclosing to individuals in social or personal relationships. Conclusion: The findings provide preliminary insight into how different considerations may be prioritized when navigating NSSI disclosure, in a way that may be tailored to different contexts. For clinicians, the findings highlight that clients may expect tangible forms of support and nonjudgment in the event that they disclose their self-injury in this formal setting.